Bentuk Tari Dedari Dalam Tradisi Makenak-Kenakan Di Pura Desa, Desa Penatahan, Penebel, Tabanan - Hani Yustia; Dyah Kustiyanti; Suminto Suminto (Jurnal IGEL : Journal Of Dance, 2021)
The Makenak-kenakan tradition is a symbol of offering, joy, and embodiment as an expression of geatitude to Ida Sang Hyang Widhi Wasa for being given an abundance of produce, avoiding disasters, and hoping to avoid disease outbreaks. This dress-up tradition is carried outby prasayang Ida Batara (a group of sutri penyungsung) the Penatahan tradisional village temple using a series of ritual processes that are carried out with a sincere sense of sincerity. The Dedari dance has certain meaningful symbols. Symbols are a major component of culture. Everything that humans see and experience can be translated into symbols that we can all understand. The Dedari dance is danced by seven dancers who are alive niskala symbolizes the seven widyadari who came down from heaven. Dedari dance is a sacred dance that is performed in the Dewa Yadnya ceremony in Penatahan village. The Dedari dance is one of the dances in the Makenak-kenakan tradition which is sacred in the village of Penatahan, Penebel, Tabanan. This dance is accompanied by gamelan Gong Kebyar. Talking about the problem of form, it is explained about the structure, the dancers of the Dadari dance, the various movements of the Dedari dance, make up, and fashion, accompaniment music, and the Dedari dance performance place, as well as the Dedari dance symbol. Dedari dance research is composed of several theories and qualitative research methods. The theory used in this research is aesthetic and functional theory. The researcher dug up information from several community leaders and residents of the Penatahan village which was then described back toin writing. Key words : Makenak-kenakan tradition, Dedari dance, Form.